Efektivitas minuman kombinasi maltodekstrin dan vitamin C terhadap hitung jenis leukosit pada atlet sepak bola - Silvi Lailatul Mahfida; Istiti Kandarina; Arta Farmawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2015)
Backgrounds: The immune system changing affects the fitness. Exercise induces the immune responses, oxidative stress and tissue damage that alters leukocyte counts. Maltodextrin supplies higher energy reserves, that can improve the immune system profiles. Vitamin C as an antioxidant against tissue damage.Objective: This study aims to assess the effectiveness of a maltodextrin and vitamin C combination drink on leukocyte differential count after exercise.Method: This study was quasi-experimental with the within-subject design. Subjects were 14 collegiate football players of the State University of Yogyakarta and fulfilled the inclusion and exclusion criteria. Subjects were selected with a purposive sampling. Subjects received a combination of 15% maltodextrin and 250 mg of vitamin C beverage, 300 mL. Subjects did wash out for 6 days, then received placebo beverage (300 mL plain water). Subjects drank 30 minutes before and 5 minutes after physical exercise. Exercise loads were yoyo intermittent test and run gradually until 80 HRmaks. Blood samples were taken immediately and 30 minutes after exercise.Results: In the administration of intervention beverage, immediately to 30 minutes after exercise neutrophils increased (p=0,006); lymphocytes decreased (p=0.015); monocytes decreased (p=0.000); and eosinophils decreased (p=0.613). In the administration of placebo beverage, immediately to 30 minutes after exercise, neutrophils increased (p=0.359); lymphocytes decreased (p=0.257); monocytes decreased (p=0.146); and eosinophils increased (p=0.549). Neutrophils (p=0.003) and monocyte (p=0.003) had significant difference between both administration drink at 30 minutes after exercise. Lymphocyte and monocyte significantly decrease (p<0.05) at intervention than placebo.Conclusion: Maltodextrin and vitamin C combination drink effect on the decreasing of lymphocyte and monocyte 30 minutes after exercise.